2013
DOI: 10.1007/s00056-012-0112-1
|View full text |Cite
|
Sign up to set email alerts
|

Class II treatment by extraction of maxillary first molars or Herbst appliance: dentoskeletal and soft tissue effects in comparison

Abstract: Both treatment methods were successful and led to a correction of the Class II division 1 malocclusion. Whereas for upper first molar extraction treatment more dental and maxillary effects can be expected, in case of Herbst treatment skeletal and mandibular effects prevail.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
17
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 29 publications
2
17
0
Order By: Relevance
“…This effect is often observed with the use of fixed functional appliances, similar finding in other studies was reported after using PowerScope in treatment of Class II malocclusion (6,7) significant reduction in SNA was also reported with the use of Herbst appliance (10) as well as with Jasper Jumper (11) and after treatment with AdvanSync appliance (12,13) Regarding the mandible there was significant anterior displacement demonstrated by statistically significant increase in SNB (P<0.001), Similar finding was reported in other studies using PowerScope Class II corrector (6)(7)(8)(9) same results were demonstrated with TFBC (14)(15)(16) and also with Herbst appliance (5,10,22) and with mandibular protraction appliance (17) . However other studies demonstrated different results as with MARA (18) .…”
Section: Regarding the Skeletal Changessupporting
confidence: 86%
See 1 more Smart Citation
“…This effect is often observed with the use of fixed functional appliances, similar finding in other studies was reported after using PowerScope in treatment of Class II malocclusion (6,7) significant reduction in SNA was also reported with the use of Herbst appliance (10) as well as with Jasper Jumper (11) and after treatment with AdvanSync appliance (12,13) Regarding the mandible there was significant anterior displacement demonstrated by statistically significant increase in SNB (P<0.001), Similar finding was reported in other studies using PowerScope Class II corrector (6)(7)(8)(9) same results were demonstrated with TFBC (14)(15)(16) and also with Herbst appliance (5,10,22) and with mandibular protraction appliance (17) . However other studies demonstrated different results as with MARA (18) .…”
Section: Regarding the Skeletal Changessupporting
confidence: 86%
“…Similar results were reported with PowerScope in other studies (6,8,9) as well as with TFBC (14,16) . Nearly all studies on FFAs that reported its effect on soft tissues revealed the same (10,22) .…”
Section: Regarding the Dento-alveolar Changesmentioning
confidence: 98%
“…In some studies, there were significant changes in the nasolabial angle resulting from tooth extraction (22,23). However, this study concurs with the study of Janson et al (24).…”
Section: Discussionsupporting
confidence: 91%
“…14,15,18 Comprehensive orthodontic treatment can effectively provide true mesial translation movement of maxillary second permanent molars following extraction of the maxillary first permanent molars. 11,28 The combination of space created through extractions and controlled bodily mesialisation of the maxillary second permanent molars may also encourage the spontaneous eruption of maxillary third permanent molars from a previously impacted position. 8 The presence, angulation, and eruption path of third maxillary molars should be carefully evaluated prior to the commencement of orthodontic treatment, particularly in patients who demonstrate significant compromise of maxillary posterior teeth.…”
Section: Discussionmentioning
confidence: 99%
“…9 Studies indicate that extraction of the maxillary first or second permanent molars can significantly improve the angulation and future eruption potential of unerupted maxillary third molars on that same side, as closure of the resultant extraction space often permits mesial bodily movement of the third molars. 10,11 This subsequent increase in eruption space may significantly reduce the frequency of third molar impaction in such cases. 10,[12][13][14][15][16][17] Although the potential for successful third molar eruption appears to be more predictable when second permanent molars are removed, well-timed extraction of maxillary first permanent molars in conjunction with active orthodontic space closure can provide pleasing outcomes in adolescent patients.…”
Section: Introductionmentioning
confidence: 99%